Additions to the taxonomy of the Auriculariales (Basidiomycota) with pedunculate basidia - Viacheslav Spirin; Vera Malysheva; Ilya Viner; Renato Lúcio Mendes Alvarenga; Tine Grebenc; Gérald Gruhn; Anton Savchenko; Django Grootmyers; Leif Ryvarden; Josef Vlasák; Karl-Henrik Larsson; R. Henrik Nilsson (MycoKeys)
In the present paper, we revise the taxonomy of the Auriculariales having pedunculate (stalked) basidia. In total, sixteen new species from Europe, East Asia, North and South America, and tropical Africa are described. They are classified among the genera Hydrophana, Mycostilla, Myxarium, Protoacia, Protohydnum, and Protomerulius. In addition, the generic affiliation of eleven extant species is re-established based on phylogenetic and/or morphological evidence. A new genus, Elmericium, is introduced to accommodate a crust-like fungus, E. alabastrinum, from East Asia; phylogenetic data place it in the vicinity of the anatomically similar poroid genera Elmerina and Protodaedalea (Auriculariaceae). The generic description of Protohydnum is amended; in its current scope, the genus encompasses several species formerly assigned to Bourdotia, Ductifera, and Exidiopsis. Available environmental data point to a wider distribution of some Protomerulius spp. and greater species diversity in the genus than currently surmised from physical fungal samples.